2013
DOI: 10.1186/1477-9560-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Protein-C deficiency presenting as pulmonary embolism and myocardial infarction in the same patient

Abstract: Plasma protein-C exerts anticoagulatory effects by inactivating factors V and VIII. Hereditary protein C deficiency is transmitted as an autosomal dominant disorder. Homozygous individuals usually develop purpura fulminans as newborns; heterozygous protein C-deficient individuals are at increased risk for venous thrombosis and pulmonary embolism. However, arterial thrombosis occurring as a result of congenital protein-C deficiency is still controversial. We describe a young patient with heterozygous protein-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…Protein C and antithrombin are natural plasma proteins that play an important role in the process of anticoagulation. Their deficiency leads to the development of procoagulant conditions, and one of the complications can be artery thrombosis [9][10][11][12][13] . The asso-ciation of stress caused by ischemia, quantified by dobutamine stress echocardiography (DSE), and changes in platelet function and other parameters of hemostasis in patients after the PCI, have not been tested so far.…”
Section: Introductionmentioning
confidence: 99%
“…Protein C and antithrombin are natural plasma proteins that play an important role in the process of anticoagulation. Their deficiency leads to the development of procoagulant conditions, and one of the complications can be artery thrombosis [9][10][11][12][13] . The asso-ciation of stress caused by ischemia, quantified by dobutamine stress echocardiography (DSE), and changes in platelet function and other parameters of hemostasis in patients after the PCI, have not been tested so far.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Protein C deficiency typically causes venous thromboembolism. However few case reports of arterial thrombosis due to congenital protein C deficiency involving cardiac and cerebral vessels in young adults have been reported, [4][5][6][7][8][9][10][11][12] though larger studies give conflicting data regarding existence of association between protein C deficiency and arterial thrombosis. [13][14][15][16][17] We report a case of congenital protein C deficiency with acute myocardial infarction in a young adult without major underlying coronary risk factors.…”
mentioning
confidence: 99%
“…1 However, many affected individuals remain asymptomatic throughout life. 12 There are several case reports of arterial thrombosis including stroke, myocardial infarction and peripheral arterial thrombosis. However, the results of larger studies have reported against protein c deficiency causing arterial thrombosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] In most patients thrombosis is rare until their early 20s, with increasing numbers experiencing thrombotic events as they reach the age of 50 years. Cases of cerebral [7,8], myocardial [7,9], and mesenteric [10] infarction caused by protein C deficiency have been reported.…”
mentioning
confidence: 99%